Jual Beli Online Perspektif Maqasid Tafsir Jasser Auda - Tilawati, Anis (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
Today, online shop is no stranger to anyone who lives in digital era, it can even be a hobby that is not just a necessity. The problem is a shift of tradition in that phenomenon, for example; there are no face-to-face moments in online shop, then how does Islam see it? For this reason, the author uses the maqasid interpretation perspective offered by Jasser Auda to researching online shop in Islam. Auda expands the maqasid theory with development and rights. The findings is include the Qur'an and the hadith do not speak explicitly related to online shop because it was not discovered at the time of the Prophet, but there are several principles of buying and selling according to Islam which can be found in the online sale and purchase transactions. Development of online shop transactions is able to realize an economy that is more practical and easier for all parties. In addition, the rights of the seller and buyer are also fulfilled in the transaction. There is the principle of tasamuh (tolerant and easy) which allows Islamic syari'at to develop according to the times.